STAFF DEVELOPMENT PROGRAMMES AND TEACHERS’ INSTRUCTIONAL TASK PERFORMANCE IN KWARA STATE PRIMARY SCHOOLS, NIGERIA - Fashiku, Christopher Oluwatoyin; Jumoke, Atere Kafayat; Abiola Yusuf, Abubakar; Florence O, Adeleke (The University of Kuningan, 2023)
ABSTRACTThe study adopted the descriptive survey research design. The Population of the study consisted of 14,206 public primary school teachers and 1,406 head teachers in the three senatorial districts of Kwara State. The sample for the study comprised 400 teachers and 40 head teachers which were selected using a multistage sampling procedure. A self-designed validated research instrument titled “Staff Development and Teachers’ Instructional Task Performance” (SDTITP) was used to collect data for the study. The reliability of the instrument was ensured with a coefficient index of 0.77. Data collected were analyzed using descriptive statistics of frequency counts and percentage scores. The results showed that in-service training 76.1; mentoring 68.6%, seminars 63.9%; and workshops 62.7%) were the types of development programmes available for the teachers; frequencies of conducting the programme were once every session and the mode used by the management in selecting staff for the development programmes was based on bias/prejudice 68.2%, seniority 65%, and the subject taught 72%. The study concluded that the development programmes of in-service training, mentoring, seminars, and workshops were staff development programmes used by the Kwara state Government for their primary school teachers. However, it was discovered that not all the teachers had the privilege of being selected to go for the programme. It was recommended among others that: the management should endeavour to add conferences as part of the professional development programmes made available for primary school teachers in Kwara State to enhance their pedagogic skills and competence towards meeting the expectations of the general public. Keywords: development; programmes; primary; schools; teachers’ task.